A reassessment of the relations in Malaysia between ants (Crematogaster) on trees (Leptospermum and Dacrydium) and epiphytes of the genus dischidia (Asclepiadaceae) including 'ant-plants' - Weir, J. S.; Kiew, Ruth (Wiley-Blackwell Publishing, 1986)
Three species of epiphytic Dischidia have been investigated in terms of their relationship to ants on trees. Two species, D. parvifolia and D. astephana, are associated with ants and trees in montane areas. A clear association has been found between ants of the genus Crematogaster and the tree Leptospermum flavesens. This relationship is complex and probably both organisms benefit from the association. The ants live in tunnels in the wood of the major branches and the trunk, and the entire tree is occupied by one ant colony. Trees occupied by ants are maintained by the ants substantially clear of epiphytes other than the two species of Dischidia. The potential benefits to the tree and to the ants of this association are noted. The roots of D. astephana and D. parvifolia penetrate into the cavities of these ant nests and presumably gain nutrients from waste in the ant nests. Both Dischidia species are effectively scavenging upon the waste material from the ant-tree association. The leathery dome-shaped leaves of D. astephana are not vital to the development of the scavenging habit as D. parvifolia has lens-shaped leaves, but may offer some advantage to D. astephana by the uptake of nutrients from waste deposited by the ants under the dome-shaped leaves by interception of stem flow and by uptake of gaseous waste. Ants do not nest under these leaves. Seeds of these species of Dischidia are taken by ants into the central woody area of the ant nest where they germinate. Both Leptospermum and Dischidia can be visualized as showing adaptations to a nutient-deficient tropical montane environment. These adaptations are discussed as is the need for reassessment in this genus of the term 'ant-plant', and the need for wider recognition of the 'ant-tree' relationship between Crematogaster and Leptospermum.